Tocotrienols as an Anti-Breast Cancer Agent - Madison Trujillo; Anupreet Kharbanda; Christa Corley; Pilar Simmons; Antiño R. Allen (MDPI AG, 2021)
In the past few years, breast cancer has become the most prevalent type of cancer. The majority of patients receive combinatorial chemotherapy treatments, which may result in increased risk of developing drug resistance, a reduced quality of life, and substantial side effects. Treatment modalities that could lessen the physical toll of standard treatments or act in synergy with chemotherapeutic treatments would benefit women worldwide. Research into tocotrienols has thus far demonstrated their potential to be such an agent, with tocotrienols surpassing the pharmacological potential of tocopherols. Further research using in vitro and preclinical breast cancer models to support clinical trials is needed. This review uses bibliometric analysis to highlight this gap in research and summarizes the current and future landscape of tocotrienols as an anti-breast cancer agent.